Enterprise resource planning and customer relationship management value - Ruivo, Pedro (2019)
Ruivo, P., Oliveira, T., & Mestre, A. (2017). Enterprise resource planning and customer relationship management value. Industrial Management and Data Systems, 117(8), 1612-1631. https://doi.org/10.1108/IMDS-08-2016-0340